2014
DOI: 10.18632/oncotarget.1742
|View full text |Cite
|
Sign up to set email alerts
|

Minor grove binding ligands disrupt PARP-1 activation pathways

Abstract: PARP-1 is a nuclear enzyme regulating transcription, chromatin restructuring, and DNA repair. PARP-1 is activated by interaction with NAD+, DNA, and core histones. Each route of PARP-1 activation leads to somewhat different outcomes. PARP-1 interactions with core histones control PARP-1 functions during transcriptional activation in euchromatin. DNA-dependent regulation of PARP-1 determines its localization in heterochromatin and PARP-1-dependent silencing. Here we address the biological significance of DNA-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
0
16
0
3
Order By: Relevance
“…The PNX0010 human ccRCC cell line (Kirsanov et al , 2014) was a kind gift of Dr Vladimir Khazak (Priaxon Inc.). The HUVEC cell line was obtained from ATCC.…”
Section: Methodsmentioning
confidence: 99%
“…The PNX0010 human ccRCC cell line (Kirsanov et al , 2014) was a kind gift of Dr Vladimir Khazak (Priaxon Inc.). The HUVEC cell line was obtained from ATCC.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we found that breast (BT474), prostate (PC3), and kidney (PNX0010) cancer cells show an unusually high level of PARP-1 activity (Kirsanov et al, 2014). Therefore, we used these cell lines to test the efficacy of PARP-1 inhibition by new and classical inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…To accomplish this, we employed a blind screen of a random small- molecule collection containing 50,000 compounds. As noted above, PARP-1 can be regulated by competing for binding with NAD (D'Amours et al, 1999), as well as by two additional routes: obstruction of PARP-1 binding with DNA (Kirsanov et al, 2014) and disruption of PARP-1 interaction with histone H4 (Pinnola et al, 2007). The latter rout of activation is highly specific to PARP-1.…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время эффекты дестабилизации хроматина ДНК-тропными агентами были описаны лишь для нового противоопухолевого препарата CBL0137 [17,18] и ряда узкобороздочных лигандов (УБЛ) [19]. Причем при действии как CBL0137, так и УБЛ наблюдалось повышение уровня экспрессии ретротранспозонов и других повторяющихся последовательностей ДНК.…”
Section: Introductionunclassified